2019
DOI: 10.1007/s00787-019-01346-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and environmental influences on attention-deficit/hyperactivity disorder symptoms in Chinese adolescents: a longitudinal twin study

Abstract: Attention-deficit/hyperactivity disorder (ADHD) is a highly heritable neurodevelopmental disorder. However, no study has examined genetic and environmental influences in the longitudinal developmental course of ADHD symptoms in a non-Western population. This study investigated changes of genetic and environmental influences and their contributions to the stability and change of ADHD symptoms of hyperactivity/impulsivity and inattention in Chinese adolescent twins. A prospective sample of 602 twin pairs (48% ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 58 publications
(143 reference statements)
0
10
0
Order By: Relevance
“…Prior evidence suggests that ADHD has a range of negative outcomes on individuals, as well as economic burdens on families and society. 3,4 Because environmental factors are associated with ADHD, 5 identifying such factors may be useful for reducing ADHD symptoms, especially considering that environmental factors are generally modifiable.…”
Section: Introductionmentioning
confidence: 99%
“…Prior evidence suggests that ADHD has a range of negative outcomes on individuals, as well as economic burdens on families and society. 3,4 Because environmental factors are associated with ADHD, 5 identifying such factors may be useful for reducing ADHD symptoms, especially considering that environmental factors are generally modifiable.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, many conclusions from twin research may not extend to other populations. For example, a recent study of ADHD traits in Chinese adolescent twins found smaller genetic and larger shared environmental influences compared to previously reported estimates in North American and European populations (Zheng, Pingault, Unger, & Rijsdijk, 2020), highlighting the necessity of collecting samples from diverse populations and suggesting that the contribution of environmental influences to ADHD may vary by societal and contextual factors.…”
Section: Quantitative Genetic Studies Of Adhdmentioning
confidence: 72%
“…For example, a recent study of ADHD traits in Chinese adolescent twins found smaller genetic and larger shared environmental influences than previously reported in Western populations (Zheng et al, 2020), highlighting the necessity of collecting globally representative samples and suggesting that the contribution of environmental influences to ADHD may vary by societal/contextual factors.…”
Section: Quantitative Genetic Studies Of Adhdmentioning
confidence: 87%
“…In fact, in older age participants such as in the present study, other sources of support, especially friends, should come into play, but this was not the case. The reason perceived as to why family support prevailed, despite the participants being emerging adults, may have been the fact that the participants live in a collectivistic society and are influenced by Thai family tradition; this influence is present in many cultures, especially in Asian countries [ 50 , 51 , 52 ]. Compared with medical students from Western cultures, the role of the family is distinctively predominant [ 53 ].…”
Section: Discussionmentioning
confidence: 99%